Los colegios sacerdotales durante la época Triunviral (43-31 A.C.) como instrumento para premiar lealtades - Pina Polo, Francisco (2018)
On November 43 the triumvirate was established. Among the powers conceded to the triumvirs was the right to appoint at least some of the annual magistrates. The triumvirs used appointments to magistracies as a way of rewarding individuals who had been loyal to them in preceding years. The same thing happened with the priestly colleges. The priesthoods served the new political elite as a springboard for social elevation. The triumvirs exploited their power to convert both magistracies and priesthoods into an instrument for rewarding loyalties and thus to form a new loyal aristocracy, which after Actium essentially became an aristocracy loyal to the future Augustus.
Keywords: Sacerdocio; Roma -- Historia -- 43-31 a.C. (Guerra civil)